Design and control of a parallel mechanism haptic master for robot surgery using magneto-rheological clutches and brakes. (November 2018) - Cha, Seung-Woo; Kang, Seok-Rae; Hwang, Yong-Hoon; Choi, Seung-Bok; Lee, Yang-Sup; Han, Moon-Sihk
This article presents tracking control performances of the repulsive force and torque of a haptic master with 6 degrees of freedom, which can be applied to robot-assisted minimally invasive surgeries. The proposed haptic master is activated by two types of actuators that use magneto-rheological fluid: magneto-rheological clutch and magneto-rheological brake. The body segment (or lower part) of the haptic master generates the repulsive forces for the three translational axes using the magneto-rheological clutch, while the wrist segment (or upper part) generates the repulsive torque for the three rotational axes through the use of the magneto-rheological brake. After analyzing the kinematic and dynamic equations, an appropriately sized haptic master is designed and manufactured. The field-dependent force and torque characteristics of the magneto-rheological actuators are experimentally investigated. Then, for successful tracking control performances, a fuzzy plus proportional–integral–derivative feedback controller is used for the repulsive force while a feed-forward controller associated with a hysteretic compensator for the repulsive torque. The effectiveness of the proposed 6-degree-of-freedom haptic master is experimentally validated by demonstrating high tracking accuracy of the force and torque.